Transcriptome analysis of jejunal mucosal tissue in breeder hens exposed to acute heat stress - Yongcai Zhu; Satoshi Kubota; Phocharapon Pasri; Sitthipong Rakngam; Supattra Okrathok; Chayanan Pukkung; Shenglin Yang; Sutisa Khempaka (Poultry Science)
Heat stress (HS) severely compromises intestinal barrier function in poultry, resulting in significant production losses. This study aimed to explore the molecular response of the small intestine to acute HS in breeder hens. Fifty 28-week-old breeder hens were raised individually in a cage and randomly assigned to control and heat-treated groups (25 hens each). Control group hens were maintained at thermoneutral conditions (23°C) and heat-treated group hens were subjected to acute HS (36°C for a 6-h). The heart rate and cloacal temperature were measured in all hens. The jejunal mucosa tissues were collected from 12 randomly selected hens per group for transcriptomic analysis. The acute HS induced significant physiological alterations, with a marked increase in the heart rate and cloacal temperature in hens (P = 0.001). Transcriptome analysis revealed 138 genes with altered expression patterns under acute HS conditions. Of these, 75 genes including heat shock proteins (HSPs) showed upregulated expression, while 63 genes including a key bile acid transport molecule (SLC10A2) exhibited downregulated expression. Functional analysis through gene ontology classification, pathway mapping via the Kyoto encyclopedia of genes and genomes, and protein interaction networks identified several important regulatory genes in thermal response (HSPA8 and HSPA2), energy homeostasis and fat metabolism (PDK4, PPARA, and CD36), glucose transport (SLC2A5), and cholesterol synthesis pathway (SQLE, CYP51A1, and HSD17B7). The findings suggest that acute HS might affect energy utilization, fat metabolism, and glucose transport mechanisms in the jejunal mucosa of breeder hens. The upregulation of HSPs appears to serve as a protective mechanism, potentially preserving intestinal nutrient processing capacity under acute HS. These findings provide foundational knowledge for further investigation into the molecular mechanisms governing HS responses in avian intestinal function and may inform strategies for maintaining gut health in commercial poultry operations exposed to environmental challenges.